The Relationship Between the Intensity of TikTok Usage and Students' Politeness Behavior at SMA Muhammadiyah 3 Surabaya - Muhammad Anwar Ibrahim; Moch Charis Hidayat; Shokhibul Arifin (Educia Journal, 2026)
The purpose of this study was to examine how the polite behavior of students at Muhammadiyah 3 High School Surabaya towards parents and teachers is related to the amount of time they spend on TikTok. This study used a quantitative correlation method. Thirty students were randomly selected to form the sample. A questionnaire was used to collect data, and SPSS was used to analyze the results using simple linear regression. The results showed that “each instrument is valid and reliable. Linearity and normality tests indicate that the data have a linear relationship and are normally distributed. However, the results of the simple linear regression test showed a significance value of 0.244 (> 0.05), which indicates that students' polite behavior is not substantially affected by how much they use TikTok. The variable of TikTok use only accounts for about 4.8% of students' polite behavior, with other factors outside the scope of this study reaching 95.2%, according to the coefficient of determination (R-squared) value of 0.048. In conclusion, students' polite behavior is not primarily influenced by how much time they spend on TikTok.” For students to use social media responsibly, the involvement of parents and teachers in monitoring and character education is very important.